Factors Related to the Utilization of Birth Waiting House by Delivery Women in the Working Area of Puskesmas Treatment, Padang City - Uliy Iffah; Miranie Safaringga; Rani Shabrina; Laila Hijradesy Ridwan (Journal of Social Research, 2023)
Birth Waiting Home (RTK) is a government program that aims to reduce maternal mortality. But in reality, there are still many people who do not take advantage of this facility. The purpose of this study was to analyze the factors related to the use of maternity waiting homes (RTK) by mothers in the city of Padang. This research is explanatory survey research conducted in four treatment centers in the city of Padang. The research sample was 185 mothers who gave birth in January-July 2022 at four Padang City Health Centers. Data collection tool using a questionnaire. The data analysis method used is chi-square at the 95% level of confidence. The results of the study show that none of the respondents used RTK. Knowledge, attitude, parity, mileage, and health insurance are not related to the use of maternity waiting homes (RTK). It is recommended to the Padang City Health Office to carry out routine supervision of the implementation of work programs related to maternal and child health, especially the use of birth waiting for homes (RTK) in all health centers in Padang City.